Modification of TiO2Nanotube Arrays with N Doping and Ag Decorating for Enhanced Visible Light Photoelectrocatalytic Degradation of Methylene Blue - Aritonang, Anthoni Batahan; Krisnandi, Yuni K.; Gunlazuardi, Jarnuzi (International Journal on Advanced Science, Engineering and Information Technology, 2018)
The Ag/N-TiO2 nanotube arrays photocatalyst have been successfully fabricated by in-situ anodization method and followed by calcining at 450oC under N2 atmospheric condition.The inner diameter, wall thickness, and length of the nanotube arrays are approximately 65 nm, 15 nm, and 900 nm, respectively. Ag nanoparticles with diameter around 20-30 nm are deposited on the surface of the N-TiO2 by an electrochemical deposition method. Compared with the TiO2 nanotube arrays, the Ag/N-doped TiO2 showed a significant enhancement of photoelectrocatalytic (PEC) degradation on methylene blue (MB), was about 92% for 240 min under visible light irradiation. The kinetic constant of Ag/N-doped TiO2 electrode was about 9 times higher than TiO2. The enhanced photocatalytic activity under visible light irradiation of Ag/N-doped TiO2 is a synergistic effect of N-doping and Ag nanoparticles deposited. Furthermore, the kinetic constant PEC degradation of MB is a contribution of photo-generated electron-hole separation efficiency, due to bias potential which was applied to the surface of the electrode. The Ag/N- TiO2 is a promising photocatalyst for organic pollutant degradation which is visible light responsive.